The Effects of α-Lipoic Acid against Testicular Ischemia-Reperfusion Injury in Rats - Seda Ozbal; Bekir Ugur Ergur; Guven Erbil; Isıl Tekmen; Alper Bagrıyanık; Zahide Cavdar (The Scientific World Journal)
Testicular torsion is one of the urologic emergencies occurring frequently in neonatal and adolescent period. Testis is sensitive to ischemia-reperfusion injury, and, therefore, ischemia and consecutive reperfusion cause an enhanced formation of reactive oxygen species that result in testicular cell damage and apoptosis. α-lipoic acid is a free radical scavenger and a biological antioxidant. It is widely used in the prevention of oxidative stress and cellular damage. We aimed to investigate the protective effect of α-lipoic acid on testicular damage in rats subjected to testicular ischemia-reperfusion injury. 35 rats were randomly divided into 5 groups: control, sham operated, ischemia, ischemia-reperfusion, and ischemia-reperfusion +lipoic acid groups, 2 h torsion and 2 h detorsion of the testis were performed. Testicular cell damage was examined by H-E staining. TUNEL and active caspase-3 immunostaining were used to detect germ cell apoptosis. GPx , SOD activity, and MDA levels were evaluated. Histological evaluation showed that α-lipoic acid pretreatment reduced testicular cell damage and decreased TUNEL and caspase-3-positive cells. Additionally, α-lipoic acid administration decreased the GPx and SOD activity and increased the MDA levels. The present results suggest that LA is a potentially beneficial agent in protecting testicular I/R in rats.